Maternal and Perinatal Outcomes of Singleton Term Breech Vaginal Delivery at a Tertiary Care Center in Nepal: A Retrospective Analysis - Tulasa Basnet; Baburam Dixit Thapa; Dipti Das; Ramesh Shrestha; Sarita Sitaula; Anu Thapa (Hindawi Limited, 2020)
Background. Breech presentation is associated with increased rates of maternal and perinatal morbidity regardless of mode of delivery. After the results of Term Breech Trial, most of the countries adopted the protocol of cesarean section for term breech delivery because of which breech vaginal delivery is becoming rare. The aim of this study is to evaluate short-term maternal and perinatal outcomes of breech vaginal delivery at a tertiary care hospital in Nepal. Methods. A retrospective review of case records of all women who had vaginal breech delivery from April 13, 2016, to April 12, 2018, was conducted, over a period of two years. Available demographic variables, obstetric characteristics, details of labor, postpartum complications, and perinatal complications were recorded and analyzed. Results. Out of 21,768 cases of deliveries during the study period, the incidence of term breech deliveries was 528 (2.4%) among which the mode of only 84 (17.8%) deliveries was vaginal. Most of the deliveries were unplanned and were conducted because emergency cesarean section could not be performed. Three (3.6%) women had postpartum hemorrhage, and four (4.8%) had entrapment of aftercoming head, two of them requiring Dührssen incisions. Adverse perinatal outcomes were seen in 23.8% of such deliveries with <7 APGAR score at 5 minutes in 20.2%, neonatal admission in 17.7%, and perinatal mortality in 8.3%. The perinatal mortality was significantly associated with birthweight less than 2500 grams as compared to birthweight ≥2500 grams (21.1% versus 4.6%; P=0.043). Conclusion. The perinatal outcomes for vaginal breech delivery are grave with our existing health facilities, especially when the deliveries are not well planned.